Back Cover: Polymer‐Templated Formation of Polydopamine‐Coated SnO2 Nanocrystals: Anodes for Cyclable Lithium‐Ion Batteries (Angew. Chem. Int. Ed. 7/2017). Issue 7 (23rd January 2017) - Jiang, Beibei; He, Yanjie; Li, Bo; Zhao, Shiqiang; Wang, Shun; He, Yan‐Bing; Lin, Zhiqun
Abstract : With great power comes great color SnO2 nanocrystals coated with protective polydopamine appear red when fully charged and green in a discharged state. In their Communication onpage 1869 ff., Z. Lin et al. describe polymer‐template‐guided formation of SnO2 nanocrystals. The material was applied as an anode in lithium‐ion batteries––achieving excellent rate capability, long‐term stability, and operability over a range of current densities.